Patronat parafii w dekanacie szadkowskim w drugiej połowie XVIII w. - Różański, Ks. Mieczysław (Biuletyn Szadkowski, 2010)
The right of patronage in Church law was understood as a set of rights and responsibilities with regard to a benefice. As benefices were mostly located on the founder’s estate, it became customary that the owner (or owners) of the locality where the parish church was situated was the parish patron. A major visible element of exercising the right of patronage was presentation to the bishop of clergymen to be considered for granting vacant benefices. Of the 19 parishes existing in Szadek decanate in the first half of the 16th century, two churches had royal patronage, six – ecclesiastical, and the most of them (11) had noblemen as patrons. In the second half of the 18th century the number of parishes in the decanate reached 27 as a result of further foundations by members of the nobility. The article presents, on the basis of available sources, the patrons of the parishes as in the second half of the 18th century.